A review on binary metal sulfide heterojunction solar cells - Moon, Dong Gwon; Rehan, Shanza; Yeon, Deuk Ho; Lee, Seung Min; Park, Sun Jae; Ahn, SeJin; Cho, Yong Soo (Solar energy materials and solar cells, 2019)
Metal sulfides have been the subject of extensive research owing to their electro-optical properties that are suitable for photovoltaic applications. In particular, low-cost binary metal sulfides including Sb2S3, SnS, PbS, Cu2S, Ag2S, Bi2S3 and FeS2 have been of interest as light absorbing materials in thin film solar cells. Despite numerous efforts devoted to the study of these materials over several decades, many technical issues and obstacles are yet to be overcome to render binary metal sulfides become a leading player in the area of thin film solar cells. One such issue is the low efficiency of solar cells built with binary metal sulfides, and hence, it is imperative to obtain a deeper understanding of the key mechanisms responsible for the loss of efficiency of such solar cells to achieve rapid improvement in the device performance. In this review, we describe the general technical progress of thin film solar cells based on binary metal sulfides and highlight the existing technical challenges toward improving the quality of the absorber films, junction characteristics, and device structure.